Clinical Usefulness of Bioavailable Vitamin D and Impact of GC Genotyping on the Determination of Bioavailable Vitamin D in a Korean Population - Hyun-Young Kim; Jin Hyun Kim; Myeong Hee Jung; In Ae Cho; Youngjin Kim; Min-Chul Cho (International Journal of Endocrinology)
Background. Bioavailable 25-hydroxy vitamin D (25(OH)D) has been suggested for the accurate determination of vitamin D status. The purpose of this study was to determine the utility of bioavailable 25(OH)D in assessing vitamin D status when vitamin D-binding protein (VDBP) was significantly altered by pregnancy and liver cirrhosis (LC). The role of genotyping of GC, a gene encoding VDBP, in the determination of bioavailable 25(OH)D concentration in a Korean population was also evaluated. Methods. This prospective study enrolled a total of 136 subjects (53 healthy controls, 45 patients with LC, and 38 pregnant women) from 2017 to 2018. The concentrations of total 25(OH)D and VDBP were measured, and bioavailable 25(OH)D concentrations were calculated. GC genotyping was performed to determine rs4588 and rs7041 polymorphisms. Clinical and laboratory data were compared among the three groups of subjects. Results. Median VDBP and total 25(OH)D concentrations were 165.2 μg/ml and 18.5 ng/ml in healthy controls, 76.9 μg/ml and 10.5 ng/ml in patients with LC, and 368.9 μg/ml and 17.7 ng/ml in pregnant women, respectively. Compared with controls, patients diagnosed with LC had significantly lower VDBP and total 25(OH)D concentrations (all P<0.001) while pregnant women had significantly higher VDBP concentrations (P<0.001). Although total 25(OH)D concentrations in pregnant women were similar to those in controls (P=0.394), their bioavailable 25(OH)D concentrations were significantly lower (1.2 vs. 3.0 ng/ml; P<0.001). Among all the three groups combined, the genotype-specific bioavailable 25(OH)D and the genotype-independent bioavailable 25(OH)D concentrations did not differ significantly (P=0.299). Conclusions. Our study has demonstrated that bioavailable 25(OH)D concentration reflects vitamin D status more accurately than the total 25(OH)D concentration, especially in pregnant women. In addition, GC genotyping did not significantly affect bioavailable 25(OH)D concentration. Therefore, if VDBP concentration is significantly altered, the measurement of bioavailable 25(OH)D concentration might facilitate the accurate determination of vitamin D status. However, GC genotyping might be unnecessary.